First records of Triatoma rubrofasciata (De Geer, 1773) (Hemiptera, Reduviidae) in Foshan, Guangdong Province, Southern China - Qin Liu; Yun-Hai Guo; Yi Zhang; Zheng-Bin Zhou; Liang-Liang Zhang; Dan Zhu; Xiao-Nong Zhou (BMC, 2017)
Abstract Background Triatomines, also known as kissing bugs, which are found throughout the world and especially in Latin America, are well known natural vectors that transmit American trypanosomiasis, also called Chagas disease. In China, the presence of two species of Triatoma (Triatoma rubrofasciata and T. sinica) was recorded in the past. Due to the growing population and the increasing risk of the global spread of Chagas disease, triatomines became a potential public health nuisance, and in 2016, we started monitoring triatomine activities in southern China. Methods Triatomine specimens were collected by the National Institute of Parasitic Diseases, Chinese Center for Disease Control and Prevention, and identified by their morphological characteristics under a dissecting microscope. In addition to morphological analysis, the genomic DNA of the specimens was extracted, and the mitochondrial 16S rRNA, the cytochrome b (CytB) gene and the nuclear ribosomal 28S rRNA gene were PCR-amplified to analyze and confirm the species genetically. Results One female adult insect and one male adult insect were collected in a dwelling in the rural area of Shunde County, Foshan City, Guangdong Province, China (22°42'44.63"N, 113°08'45.34"E). The results from the morphological and genetic analyses indicated that these triatomines were T. rubrofasciata. Conclusions This is the first time that the occurrence of T. rubrofasciata has been confirmed in Foshan City, Guangdong Province in southern China. Further studies are needed to reach a clearer understanding of the ecology of this species of triatomine, since it has been found to be naturally infected by Trypanosoma cruzi and T. conorhini and there is evidence of its domiciliation capabilities.